Centralization as the key survival benefit in acute neonatal surgery - Besendörfer, Manuel; Günster, Simone; Linz, Katja; Reutter, Heiko Martin; Diez, Sonja (Frontiers in Pediatrics, 2024)
Introduction. Centralization of neonatal surgical care for congenital malformations is already under discussion. Acute care of neonatal emergencies in perinatal centers with affiliated hospitals is not uniformly regulated in Germany. Materials and Methods. Analyses are based on acute pediatric surgical care at four affiliated hospitals of a perinatal center. Epidemiologic data and outcome parameters "survival," "intracerebral hemorrhage," and "revision of surgical indication" are assessed. Comparison is made between patients receiving surgical treatment at affiliated hospitals (group A) and patients with transfer to the university center for therapy in case of surgical indication for gastrointestinal diseases (group B).Results. 17 group A-patients are compared to 40 group B-patients. Comparison of epidemiological data reveals no significant differences. There is a survival advantage with transfer to the university center (mortality of 29% in group A vs. 2% in group B, p=0.007). Intracerebral hemorrhage occurred more frequently in externally treated patients (group A 24% vs. group B 2%, p=0.024). Surgical indication was revised in 30% of group B at the university center (p=0.011) with consecutive successful conservative treatment.Transfer of patients at the beginning of the acute phase of gastrointestinal diseases is key to optimize the quality of neonatal surgical care. However, larger population studies should confirm the presented results, discuss restricting factors of real care structures and should rule out bias in triage of patients.